Kemampuan Komunikasi Matematis ditinjau dari Self-Confidence melalui Model Teams Games Tournament berbantuan Baamboozle - Indrawan, Tarista Amelia Putri; Munahefi, Detalia Noriza (Circle: Jurnal Pendidikan Matematika, 2025)
This study aims to (1) test the effectiveness of using a Teams Games Tournament learning model assisted by Baamboozle on students’ mathematical communication skills; (2) test the effect of self-confidence on mathematical communication skills; and (3) obtain a description of students’ mathematical communication skills who use the Teams Games Tournament learning model, reviewed from their self-confidence. This research is a mixed-method study with a sequential explanatory design. The results show that (1) the Teams Games Tournament learning model assisted by Baamboozle is effective on mathematical communication skills; (2) there is a positive influence of self-confidence on students’ mathematical communication skills by 40.1%; and (3) the description of mathematical communication skills is as follows: (a) students with high self-confidence tend to meet all three indicators of mathematical communication skills, (b) students with moderate self-confidence fulfill two indicators of mathematical communication, and (c) students with low self-confidence only meet the indicator of students’ ability to express real-world problems into mathematical ideas.